2022
DOI: 10.3390/cells11050802
|View full text |Cite
|
Sign up to set email alerts
|

Impaired p53-Mediated DNA Damage Response Contributes to Microcephaly in Nijmegen Breakage Syndrome Patient-Derived Cerebral Organoids

Abstract: Nijmegen Breakage Syndrome (NBS) is a rare autosomal recessive genetic disorder caused by mutations within nibrin (NBN), a DNA damage repair protein. Hallmarks of NBS include chromosomal instability and clinical manifestations such as growth retardation, immunodeficiency, and progressive microcephaly. We employed induced pluripotent stem cell-derived cerebral organoids from two NBS patients to study the etiology of microcephaly. We show that NBS organoids carrying the homozygous 657del5 NBN mutation are signif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Further expansions in iPSC research have increasingly revealed the multifaceted use of these cells in modeling various diseases in vitro [ 17 , 18 , 19 , 20 , 100 ]. With the development of iPSCs, researchers have been able to replicate many diseases, including Parkinson’s disease, Nijmegen Breakage Syndrome, and Alzheimer’s disease, all by generating different types of cells that mimic the in vivo environment very closely [ 19 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. For instance, deriving iPSCs from patients with genetic-based neurological conditions and differentiating them into neurons opens up more possibilities to closely observe the pathological mechanisms underlying the disease in vitro [ 106 , 110 , 111 , 112 ].…”
Section: Bind and Cns Disease Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further expansions in iPSC research have increasingly revealed the multifaceted use of these cells in modeling various diseases in vitro [ 17 , 18 , 19 , 20 , 100 ]. With the development of iPSCs, researchers have been able to replicate many diseases, including Parkinson’s disease, Nijmegen Breakage Syndrome, and Alzheimer’s disease, all by generating different types of cells that mimic the in vivo environment very closely [ 19 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. For instance, deriving iPSCs from patients with genetic-based neurological conditions and differentiating them into neurons opens up more possibilities to closely observe the pathological mechanisms underlying the disease in vitro [ 106 , 110 , 111 , 112 ].…”
Section: Bind and Cns Disease Modelsmentioning
confidence: 99%
“…Genetic mutations affect cell type, cell behavior, their interactions, neuronal network, and components of the various neurodevelopmental and physiological processes. iPSC-derived brain organoids afford studying these genetic mutations and multi-faceted brain diseases [ 108 , 148 , 151 , 152 , 153 ]. Moreover, being cultured in vitro, organoids provide easy accessibility genetically and for live assays [ 154 ].…”
Section: Bind and Cns Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this Special Issue, we have collected articles that emphasise the wide application possibilities of iPSCs. The publications cover diseases of brain [ 2 , 3 , 4 , 5 ], kidney [ 6 ], blood [ 7 , 8 ], cartilage [ 9 ] and primordial germ cells [ 10 ] in 2D and 3D models.…”
mentioning
confidence: 99%
“…Martins et al employed 3D brain organoids to model the rare neurodevelopmental disease Nijmegen Breakage syndrome (NBS) [ 4 ]. This disease is caused by mutations in the DNA double-strand repair gene nibrin.…”
mentioning
confidence: 99%